Patterns in Language and Linguistics New Perspectives on a Ubiquitous Concept - Busse, Beatrix; Moehlig-Falke, Ruth (Topics in English linguistics ;, 2019)
Despite its importance for language and cognition, the theoretical concept of »pattern« has received little attention in linguistics so far. The articles in this volume demonstrate the multifariousness of linguistic patterns in lexicology, corpus linguistics, sociolinguistics, text linguistics, pragmatics, construction grammar, phonology and language acquisition and develop new perspectives on »pattern« as a linguistic concept.